1995
DOI: 10.1007/bf02382870
|View full text |Cite
|
Sign up to set email alerts
|

Population census of the chimpanzees in the Kalinzu Forest, Uganda: Comparison between methods with nest counts

Abstract: ABSTRACT. The population of chimpanzees in the Kalinzu Forest, Uganda was censused with nest counts using the line-transect method. Four methods were examined to estimate density. The estimated densities, ranging from 2.0 to 4.7 chimpanzees per km 2, all indicated a high population density, in comparison with other chimpanzee habitats. Moreover, the density in the logged area of the Kalinzu Forest was higher than that in the unlogged area. Several factors are thought to contribute to the high density in the Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(96 citation statements)
references
References 14 publications
2
92
0
1
Order By: Relevance
“…Il est important de distinguer les différentes caractéristiques des nids lorsque des espèces sont sympatriques (Tutin et al 1995). Sanz et al (2007) (Plumptre et Reynolds 1994Hashimoto 1995;Furuichi et al 2001 (Tutin et Fernandez 1984). Pour prendre en compte la rapidité de dégradation de certains types de nids de gorilles, il faudrait parcourir les transects à des intervalles plus rapprochés.…”
Section: Comptage Des Nidsunclassified
“…Il est important de distinguer les différentes caractéristiques des nids lorsque des espèces sont sympatriques (Tutin et al 1995). Sanz et al (2007) (Plumptre et Reynolds 1994Hashimoto 1995;Furuichi et al 2001 (Tutin et Fernandez 1984). Pour prendre en compte la rapidité de dégradation de certains types de nids de gorilles, il faudrait parcourir les transects à des intervalles plus rapprochés.…”
Section: Comptage Des Nidsunclassified
“…7 chimpanzees per km2 (2). Moreover, I showed that the density in the logged area was higher than that in the unlogged area.…”
mentioning
confidence: 87%
“…1). between the time and means available and the precision required for this study 6,7,8 . A total of 41.16 km in 17 line transects (mean length: 2.4 km; [1.8-3.3]) distant of at least 500 m from each other, were covered in the terra firma of the Pongara peninsula (Fig.…”
Section: Study Areamentioning
confidence: 99%